The volume profile method and its theoretical connection with microeconomic theory as the main premise of its application - Chutka Jan (SHS Web of Conferences, 2021)
Research background: This article was conceived as a very valuable basis and the result of theoretical research in the field of microeconomics with a specific application. Specifically, in the article we tried to accurately describe the logic and predictive weight of the Volume profile method with reference to the exact descriptions of the functioning of the market mechanism. Purpose of the article: The aim of our paper is to describe in detail and identify the microeconomic foundations of the Volume Profile prediction tool. Methods: In the first chapter of the article, we described in detail the investigated method of volume profile. Subsequently, we described its logic, functions and detailed calculation as well as its use. We continued with a description of the basic interactions between supply and demand, as well as a description of the market mechanism. Findings & Value added: The result was an accurate identification and description of the connection between the operation of the investigated prediction method and its microeconomic basis.